The Importance-Satisfaction Matrix as a Strategic Tool for Termas de Chaves Thermal Spa Priority Improvements - Vaz, Márcia; Fernandes, Paula Odete; Ferreira, Fernanda A.; Alves, Maria José; Costa, Vânia; Nunes, Alcina (Journal of Tourism, Sustainability and Well-being, 2023)
Health and wellness tourism has gained increased interest from the public, which searches for spaces that assure health and wellness maintenance. Proof of this is the example of Termas de Chaves thermal spa, which has gradually grown demand for its products and services. In this context, this study aims to identify and analyse the attributes offered by the thermal spa since it is essential to know the customer’s preferences and satisfaction. To this end, dimensions related to the determinants of importance that influence the respondents’ satisfaction were evaluated. A questionnaire survey was applied on-site from 09 August to 20 December 2021, obtaining a total sample of 225 participants. After data collection, the importance-satisfaction matrix was applied for exploratory, descriptive analysis. The results show that customers give high overall importance and satisfaction to the attributes under study. Moreover, it was possible to identify that the factor “availability and assistance provided by human resources” presents high importance but low satisfaction. Such a conclusion indicates that it will be necessary to adapt improvement strategies to increase customer satisfaction.